Retrocardiac mediastinal foregut duplication cyst - Brian T. Craig; Eric J. Rellinger; Elizabeth G. Martinez; Syamal D. Bhattacharya; Hernan Correa; David P. Bichell; Dai H. Chung (Journal of Pediatric Surgery Case Reports, 2016)
Foregut duplications occur at various locations throughout the upper gastrointestinal tract, including the thoracic cavity. Thoracic foregut duplications are typically intimately associated with the esophagus and therefore are located in either the posterior mediastinum or in pleural cavity. Here we report a case of foregut duplication of the middle mediastinum, intimately associated with the pericardium and great vessels that contained gastric mucosa, ciliated respiratory epithelium, bronchial-type epithelium, pancreatic tissue and hepatocytes. The literature of mediastinal foregut duplications is also reviewed.